Abdominal Trauma in the Emergency Department: Patterns, Evaluation, and Management Strategies - Tahir Hamid, Khushal Khan, Farhana, M Waseem Anwar, Yasmin Usman, Muhammad Ikram (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abdominal trauma was a common presentation in the emergency department and could range from mild injuries to life-threatening conditions. Understanding the patterns of abdominal trauma was essential for effective management and improved patient outcomes. Aim: This study aimed to analyze the patterns of abdominal trauma cases in the emergency department, assess the evaluation techniques employed, and explore effective management strategies to enhance patient care. Methods: A retrospective analysis was conducted on a cohort of patients who presented with abdominal trauma at a tertiary care emergency department over three years. Patient demographics, injury mechanisms, clinical evaluations, diagnostic imaging modalities, and management strategies were reviewed and analyzed. Results: Our analysis revealed a diverse range of patterns in abdominal trauma, with the most common causes being motor vehicle accidents, falls, and interpersonal violence. Clinical evaluation techniques, such as physical examination and ultrasound, played a crucial role in the initial assessment of these patients. Advanced imaging, including computed tomography (CT) scans, enhances diagnostic accuracy. The management strategies included non-operative management for stable patients and surgical intervention for those with significant injuries. Additionally, patient outcomes were positively correlated with prompt and accurate assessment. Conclusion: Abdominal trauma in the emergency department presented a multifaceted challenge, with diverse patterns and severity. Accurate evaluation, including a combination of clinical assessment and advanced imaging, was crucial for effective management. Tailored strategies, which might include non-operative approaches, were essential to optimize patient care and outcomes. This study emphasized the importance of a systematic approach to abdominal trauma, aiming to minimize morbidity and mortality associated with these injuries. Keywords: Abdominal trauma, emergency department, injury patterns, evaluation, management strategies, diagnostic imaging, patient outcomes.